A pre-coated film

By adopting a pre-coated film with a multi-layer gradient structure, using mechanical coating technology and inorganic particles in the resin coating, the problem of insufficient thickness and uniformity of the filter layer of traditional ceramic ultrafiltration membrane is solved, and higher filtration accuracy and flux are achieved, and service life is extended.

CN114452819BActive Publication Date: 2025-03-21FOSHAN SHUNDE DISTRICT TENGYUAN ENVIRONMENTAL PROTECTION WATER CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111478035.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-06
Publication Date
2025-03-21
Estimated Expiration
2041-12-06

AI Technical Summary

Technical Problem

During the manufacturing process, traditional ceramic ultrafiltration membranes have insufficient filter layer thickness and uniformity, which leads to a contradiction between filtration accuracy and flux, and are prone to clogging and are ineffective in backflush cleaning.

Method used

A pre-coated film with a multi-layer gradient structure, including a base film, an ultrafiltration layer and a permeable support layer, is used to achieve a thinner and evenly uniform ultrafiltration layer through mechanical coating process. The ultrafiltration layer is composed of a resin coating, and the permeable support layer is composed of a resin coating, and the inorganic particles are evenly distributed. The thickness of the permeable support layer is thicker than that of the ultrafiltration layer, and the particle size of the inorganic particles increases layer by layer.

Benefits of technology

A nano-filtered water filter layer of the ultrafiltration layer is realized with a thickness deviation range of less than ±10%, which improves the filtration accuracy and flux of the ceramic ultrafiltration membrane, extends the service life, and simplifies the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114452819B_ABST
    Figure CN114452819B_ABST
Patent Text Reader

Abstract

This invention discloses a pre-coated membrane comprising a base membrane, an ultrafiltration layer, and a water-permeable support layer, wherein the base membrane, ultrafiltration layer, and water-permeable support layer are stacked sequentially. The base membrane is a plastic film. The water-permeable support layer is thicker than the ultrafiltration layer. The ultrafiltration layer is composed of a resin coating in which inorganic nanoparticles are uniformly distributed. The water-permeable support layer is also composed of a resin coating in which inorganic particles are uniformly distributed. The particle size of the inorganic particles in the water-permeable support layer is larger than that of the inorganic nanoparticles in the ultrafiltration layer. Using this invention, nanofiltration layers with a thickness of less than 0.1 micrometers can be fabricated, with a thickness deviation controlled within ±10%, achieving a level of thinness and thickness accuracy far exceeding traditional technologies. Water purification products produced using this invention can significantly reduce clogging by impurities in the water, allowing for backwashing in shorter times, with lower backwash water pressure, and producing less backwash wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a pre-coating membrane with a multi-layer gradient structure, in particular to a pre-coating membrane used for making microfiltration and ultrafiltration water purification materials, and belongs to the field of new functional materials. Background Art

[0002] At present, ceramic ultrafiltration membranes have been used in liquid filtration, concentration, and solid-liquid separation in industries such as water treatment, food processing, and biochemical engineering. In the existing ceramic membrane production process, due to the limitations of the powder stacking and sintering process, the filter holes are unevenly distributed, the pore size difference range is large, and the minimum pore size and the maximum pore size differ by dozens of times. This situation has a serious impact on the performance of ceramic ultrafiltration membranes in practical applications, and the problem is manifested in the contradiction between filtration accuracy and flux. A small pore size is beneficial to ensuring filtration accuracy, but it will easily cause clogging and rapid flux attenuation. Although a large pore size is beneficial to maintaining flux, the filtration accuracy will decrease. When the pore size range is too large, the contradiction between the filtration accuracy and flux attenuation time is difficult to reconcile.

[0003] There are many factors that affect the filtration accuracy and flux of ultrafiltration membranes, including the structural characteristics of the membrane layer, and more importantly, the thickness of the membrane layer. When the same structure but different thicknesses are used, the difference in resistance of the micro-filter channel will have an impact. The thickness of the filter layer of a high-precision filter membrane is less than 1 micron. It is very difficult to ensure that the thickness of the filter layer is controlled within the corresponding accuracy range of the membrane layer thickness using traditional processes.

[0004] Traditional ceramic ultrafiltration membranes are high-precision filter layers set on the surface of multi-gradient permeable ceramic substrates. The method is to form a thin slurry layer on the ceramic substrate by natural leveling or scraping the slurry for making the filter layer, and then enter the drying and firing stages. However, from the surface, the surface of the slurry layer that is naturally leveled or scraped is very flat, but if there are uneven surfaces on the substrate, the thickness of the slurry layer will be uneven. More slurry will be filled into the concave part of the substrate to increase the thickness of the slurry layer, while the slurry layer of the protruding part of the substrate will become thinner. Since the thickness of some ultrafiltration membrane layers is only 0.1 microns, and the flatness accuracy of the substrate surface formed by mechanical means is not at the same order of magnitude as the membrane thickness, the thickness of the membrane layer finally formed by the process of natural leveling or scraping of the slurry will have a very large thickness error ratio relative to the reference value of 0.1 microns.

[0005] The traditional technology of ceramic ultrafiltration membrane has the contradiction between filtration accuracy and flux, and the ultrafiltration layer is too thick, forming an overly long filter channel, which makes it easier for debris in the water to block the filter channel and cause backwash cleaning to be ineffective. The above problems are all caused by the poor thickness and uniformity of the filter membrane layer in the membrane manufacturing process. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a pre-coated membrane, which completely changes the original manufacturing technology and process of the ultrafiltration membrane. The pre-coated membrane can achieve a thinner and more uniform ultrafiltration layer, and can greatly improve the quality and technical performance of ceramic ultrafiltration membrane products.

[0007] The present invention can adopt the following technical scheme:

[0008] A pre-coating membrane, comprising a base membrane, an ultrafiltration layer, and a water-permeable support layer, wherein the base membrane, the ultrafiltration layer, and the water-permeable support layer are stacked in sequence; the base membrane is a plastic film; the water-permeable support layer is thicker than the ultrafiltration layer;

[0009] The ultrafiltration layer is composed of a resin coating in which inorganic nanoparticles are evenly distributed; the water-permeable support layer is composed of a resin coating in which inorganic particles are evenly distributed; the particle size of the inorganic particles in the water-permeable support layer is larger than that of the inorganic nanoparticles in the ultrafiltration layer.

[0010] The present invention can further adopt the following improvement measures to solve the problem:

[0011] One improvement is: the number of layers of the permeable support layer is at least two, and the layers are arranged and stacked in order from near to far according to the distance to the ultrafiltration layer; among two adjacent permeable support layers, the permeable support layer that is farther away from the ultrafiltration layer is thicker; the permeable support layer that is farther away from the ultrafiltration layer has a larger particle size of inorganic particles; the surface of the outermost permeable support layer is viscous or thermoplastic.

[0012] One improvement is: the base membrane has a medium release force release layer on one side adjacent to the ultrafiltration layer, and a light release force release layer on the other side; the outermost permeable support layer has a self-adhesive layer coated on its outer surface, or the resin coating of the outermost permeable support layer is directly made of self-adhesive resin.

[0013] One improvement is that the side of the base membrane adjacent to the ultrafiltration layer is a medium release layer, the outermost permeable support layer has a hot melt adhesive layer on its outer surface, or the resin coating of the outermost permeable support layer is directly made of hot melt adhesive resin.

[0014] One improvement is that the resin coating is a polyurethane resin layer, and the base film is a biaxially stretched polyester film.

[0015] One improvement is that the inorganic particles are ground from ceramic materials with porous and loose skeleton structures.

[0016] One improvement is that the inorganic nanoparticles have a particle size between 2 and 1000 nanometers.

[0017] One improvement is that: the number of layers of the water-permeable support layer is one layer, and the surface of the water-permeable support layer is sticky or thermoplastic;

[0018] The base membrane has a medium release layer on one side adjacent to the ultrafiltration layer, and a light release layer on the other side; the outer surface of the water-permeable support layer is coated with a self-adhesive layer, or the resin coating of the water-permeable support layer is a self-adhesive resin.

[0019] One improvement is that: the number of layers of the water-permeable support layer is one layer, and the surface of the water-permeable support layer is sticky or thermoplastic;

[0020] The side of the base membrane adjacent to the ultrafiltration layer is a medium release layer, the outer surface of the water-permeable support layer is coated with a hot melt adhesive layer, or the resin used in the resin coating of the water-permeable support layer is a hot melt adhesive resin.

[0021] One improvement is that the inorganic particles used in the water-permeable support layer have a particle size 3-15 times that of the inorganic particles in the previous layer.

[0022] The above technical solution has the following technical effects:

[0023] 1. The present invention adopts a mechanical coating process on the surface of the plastic film to obtain a thinner and more uniform coating than directly on the ceramic substrate by self-leveling or scraping. Especially for the ultrafiltration layer, the present invention can be used to produce a nano water filtration layer below 0.1 microns, and the thickness deviation range can be controlled within an accuracy of ±10%. Its ultra-thin degree and thickness accuracy far exceed those of traditional technologies.

[0024] 2. After the thickness of the ultrafiltration layer and the permeable support layer of the water purification product produced by the present invention becomes thinner, the filter channel (water filtration path) is shortened, which can greatly reduce the probability of debris in the water being blocked in the filter channel. Backwash cleaning can take a shorter time, lower backwash water pressure and produce less backwash sewage. More importantly, the chance of debris being stuck in the filter channel and unable to be cleared by backwashing is greatly reduced, which will greatly increase the service life of the ceramic filter membrane.

[0025] 3. The thin and uniform ultrafiltration layer of the water purification product produced by the present invention can achieve relatively close micropore diameters in all areas of the ultrafiltration layer, which fundamentally solves the contradiction between filtration accuracy and flux, and can achieve water purification with higher standards and higher efficiency.

[0026] 4. The pre-coated membrane of the present invention already includes an ultrafiltration layer and a multi-layer permeable support layer. During construction, it can be directly attached to a permeable ceramic substrate, and the base membrane can be torn off and fired directly. In addition, the structural requirements and precision requirements for the substrate are also relaxed. The entire production process is more convenient and faster than traditional processes, and the authenticity rate is greatly improved, which effectively improves product performance and quality and reduces manufacturing costs.

[0027] 5. The present invention is suitable for applying a film to the corrugated surface of a ceramic permeable substrate, and can be used to produce a ceramic ultrafiltration membrane with a larger surface value and a larger flux. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the structure of embodiment 1 of the present invention.

[0029] Figure 2 It is a structural diagram of embodiment 2 of the present invention. DETAILED DESCRIPTION

[0030] The present invention is described in detail below with reference to specific embodiments.

[0031] Example 1: Figure 1 As shown, a pre-coating membrane includes a base membrane 1, an ultrafiltration layer 2, a first water-permeable support layer 3 and a second water-permeable support layer 4. The base membrane 1, the ultrafiltration layer 2, the first water-permeable support layer 3 and the second water-permeable support layer 4 are stacked in sequence, and the base membrane 1 is a plastic film; the ultrafiltration layer 2 is composed of a resin coating, and the resin coating 21 is uniformly distributed with inorganic nanoparticles 22; the first water-permeable support layer 3 is composed of a resin coating 31, and the resin coating 31 is uniformly distributed with inorganic particles 32; and the second water-permeable support layer 4 is composed of a resin coating 41, and the resin coating 41 is uniformly distributed with inorganic particles 42. The thickness of each layer of the ultrafiltration layer 2, the first water-permeable support layer 3 and the second water-permeable support layer 4 increases in sequence, that is, the thickness of the water-permeable support layer is thicker than that of the ultrafiltration layer, and the thickness of the second water-permeable support layer is thicker than that of the first water-permeable support layer. The particle size of the inorganic nanoparticles in the ultrafiltration layer 2, the particle size of the inorganic particles in the first permeable support layer 3 and the second permeable support layer 4 increase in sequence, that is, the particle size of the inorganic particles in the permeable support layer is larger than the particle size of the inorganic nanoparticles in the ultrafiltration layer. In the first permeable support layer 3 and the second permeable support layer 4, the farther the distance from the ultrafiltration layer is, the larger the particle size of the inorganic particles; the surface of the outermost second permeable support layer 4 is sticky.

[0032] This embodiment also adopts the following improvement measures:

[0033] An improved embodiment is: the base film 1 is a biaxially oriented polyester (BOPET) film, and is coated with release layers on both sides, the side adjacent to the ultrafiltration layer 2 is a medium release force release layer 12, and the other side is a light release force release layer 11. The outer surface of the outermost permeable support layer (the second permeable support layer 4) is coated with a self-adhesive layer, or the resin coating of the outermost permeable support layer is directly made of self-adhesive resin. The medium release force can prevent the base film from being easily separated from the ultrafiltration layer, and when used in the production of water purification materials, the base film can be torn off after the pre-coated film is transferred to the ceramic substrate.

[0034] An improved embodiment is that the resin coating is a polyurethane resin layer. The rest is the same as the embodiment 1 and the above improved embodiment.

[0035] An improved embodiment is: the inorganic particles are ground from ceramic materials with porous and loose skeleton structures. The rest is the same as the embodiment 1 and the above improved embodiment.

[0036] An improved embodiment is: the inorganic nanoparticles have a particle size of 30 nanometers. The rest is the same as the embodiment 1 and the above improved embodiment.

[0037] An improved embodiment is: the particle size of the inorganic particles in the water-permeable support layer is about 5 times the particle size of the inorganic particles in the previous water-permeable support layer. The rest is the same as the embodiment 1 and the above improved embodiment.

[0038] An improved embodiment is as follows: the surface of the second water-permeable support layer 4 is sticky and coated with a self-adhesive layer 5. The rest is the same as the embodiment 1 and the above improved embodiment.

[0039] An improved embodiment is: the number of layers of the water permeable support layer is multiple, and each layer is stacked in order from near to far according to the distance to the ultrafiltration layer; of two adjacent water permeable support layers, the water permeable support layer farther from the ultrafiltration layer has a thicker thickness. The water permeable support layer farther from the ultrafiltration layer has a larger particle size of inorganic particles. The rest is the same as embodiment 1 and the above improved embodiment.

[0040] An improved embodiment is that the two sides of the base film have different surface tensions. The rest is the same as the embodiment 1 and the above improved embodiment.

[0041] An improved embodiment is: the side of the base membrane adjacent to the ultrafiltration layer is a medium release force release layer, the outermost water-permeable support layer (the second water-permeable support layer 4) has a hot melt adhesive layer on its outer surface, or the resin coating of the outermost water-permeable support layer is directly made of hot melt adhesive resin.

[0042] An improved embodiment is: the particle size of the inorganic particles in the water permeable support layer is 3-15 times the particle size of the inorganic particles in the previous water permeable support layer. The particle size of the inorganic particles in the water permeable support layer is 3-15 times the particle size of the inorganic nanoparticles in the previous ultrafiltration layer.

[0043] Working principle:

[0044] When used, the pre-coated film product of Example 1 can be rolled up. When used, a laminating machine is used to stick the sticky side on the ceramic substrate, and then the polyester base film is torn off. In this way, the water-permeable support layer of the coarsest inorganic particles of the pre-coated film is mutually attached to the water-permeable base surface of the ceramic substrate below it, and the ultrafiltration layer is located on the outermost surface. The surface of the ceramic substrate has good water permeability. After the film is attached, the ceramic substrate can be sintered at high temperature. The high temperature of the kiln will completely decompose the organic matter such as the resin left by the pre-coated film, and the remaining inorganic particles will remain on the substrate and sintered on the surface of the ceramic substrate in the original stacking relationship to become a ceramic ultrafiltration membrane product.

[0045] If the surface of the ceramic substrate is uneven, the ultrafiltration pre-coated membrane has very good softness after tearing off the polyester base membrane, and the membrane layer will also adhere to the surface of the ceramic substrate following the ups and downs, so that the thickness of the water-permeable support layer and ultrafiltration layer on the entire surface of the ceramic substrate is not affected by the surface flatness and remains consistent.

[0046] The ultrafiltration pre-coating membrane is coated with a precision coater. At present, general precision coaters can achieve a coating thickness of less than 1 micron and a thickness accuracy within ±10%. This is a coating accuracy that cannot be achieved by self-leveling the surface of a ceramic substrate or by scraping on its surface. The biaxially stretched polyester film is used as the coating base membrane, and its flatness is much higher than that of the ceramic substrate. In this way, a high-precision ultra-thin coating can be processed by a two-pronged approach of a precision coater and a smooth polyester film.

[0047] As for the ultra-high precision ultrafiltration membrane layer with an ultra-thin thickness of 0.1 microns, it has exceeded the adaptability range of the coating machine, but this ultra-thin requirement can be achieved by adjusting the ratio of inorganic nanoparticles, resin and diluent during coating. When the volume ratio of nanoparticles to resin (including diluent) is 1:10, and the coating thickness is 1 micron, the diluent and resin are respectively evaporated and pyrolyzed by high temperature during the product sintering process, leaving only 10% thickness of inorganic nanoparticles, thus achieving an ultra-thin filter layer of 0.1 microns.

[0048] The finer the inorganic nanoparticles used in the ultrafiltration layer, the higher the water filtration accuracy. This embodiment can be applied to the processing and production of ceramic ultrafiltration membranes for drinking water purification projects.

[0049] Example 2: Figure 2 As shown, Figure 2A pre-coating membrane includes a base membrane 1, an ultrafiltration layer 2, and a water-permeable support layer 3. The base membrane 1, the ultrafiltration layer 2, and the water-permeable support layer 3 are stacked in sequence, the water-permeable support layer 3 can be a layer, and the base membrane 1 is a plastic film; the ultrafiltration layer 2 is composed of a resin coating 21, and inorganic nanoparticles 22 are uniformly distributed in the resin coating 21; the water-permeable support layer 3 is composed of a resin coating 31, and inorganic particles 32 are uniformly distributed in the resin coating 31. The thickness of the ultrafiltration layer 2 and the water-permeable support layer 3 increases in sequence, that is, the thickness of the water-permeable support layer is thicker than that of the ultrafiltration layer; the particle size of the inorganic nanoparticles 22 in the ultrafiltration layer 2 and the particle size of the inorganic particles in the water-permeable support layer 3 increase in sequence, that is, the particle size of the inorganic particles in the water-permeable support layer is larger than that of the inorganic particles in the ultrafiltration layer; the surface of the outermost water-permeable support layer 3 has thermoplasticity.

[0050] This embodiment also adopts the following improvement measures:

[0051] An improved embodiment is: the base film 1 is a biaxially oriented polypropylene (BOPP) film, and the side adjacent to the ultrafiltration layer is a medium release force release layer or a light release force release layer 12. The outer surface of the water permeable support layer is coated with a self-adhesive layer, or the resin coating of the water permeable support layer is directly made of a self-adhesive resin.

[0052] An improved embodiment is that the resin in the ultrafiltration layer is polyvinyl alcohol resin.

[0053] An improved embodiment is: the inorganic particles are made by grinding a ceramic material with a porous and loose skeleton structure.

[0054] An improved embodiment is that the inorganic nanoparticles 22 used in the ultrafiltration layer 2 have a particle size of about 80 nanometers.

[0055] An improved embodiment is that the inorganic particles 32 used in the water-permeable support layer have a particle size that is about 8 times the particle size of the inorganic particles in the previous layer.

[0056] An improved embodiment is: the surface of the water-permeable support layer 3 is thermoplastic, the side of the base membrane adjacent to the ultrafiltration layer is a medium release layer, the outer surface of the water-permeable support layer is coated with a hot melt adhesive layer, or the resin coating of the water-permeable support layer is directly made of hot melt adhesive resin. The resin 31 used in this layer is a hot melt adhesive resin.

[0057] The difference between Example 2 and Example 1 is that the particle size of the inorganic nanoparticles used in the ultrafiltration layer is slightly increased, and there is only one permeable support layer. This design is suitable for occasions with slightly lower water purification requirements than Example 1. The manufacturing cost of the pre-coated membrane of Example 2 is also relatively low, and it can be used for the purification of non-drinking water projects such as landscape water or swimming pool water.

[0058] The water-permeable support layer of the pre-coated film of Example 2 has thermal adhesiveness, and the pre-coated film and the ceramic substrate can be thermally bonded together by hot pressing. When the outermost water-permeable support layer uses hot melt adhesive instead of self-adhesive adhesive, it is not sticky at room temperature, and there will be no adhesion between the bottom and the surface of the pre-coated film when the pre-coated film is made into a coil, so the non-coated surface of the base film does not need to be provided with a release layer. The advantage of the thermally adhesive pre-coated film is that its finished product can be either a coil or a sheet, so as to be suitable for different bonding operations.

[0059] The pre-coated film of the present invention has the property of being soft and can be applied to non-planar water-permeable base surfaces for pasting, including being applied to the processing and production of filter membrane products with cylindrical and corrugated surfaces.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A pre-coating film, characterized in that: The invention comprises a base membrane, an ultrafiltration layer and a water-permeable support layer, wherein the base membrane, the ultrafiltration layer and the water-permeable support layer are stacked in sequence; the base membrane is a plastic film; the water-permeable support layer is thicker than the ultrafiltration layer; The ultrafiltration layer is composed of a resin coating, in which inorganic nanoparticles are evenly distributed; the water-permeable support layer is composed of a resin coating, in which inorganic particles are evenly distributed; the particle size of the inorganic particles in the water-permeable support layer is larger than the particle size of the inorganic nanoparticles in the ultrafiltration layer; The number of layers of the water-permeable support layer is at least two, and each layer is arranged and stacked in order from near to far according to the distance to the ultrafiltration layer; of two adjacent water-permeable support layers, the water-permeable support layer farther from the ultrafiltration layer has a thicker thickness; the water-permeable support layer farther from the ultrafiltration layer has a larger particle size of inorganic particles; the surface of the outermost water-permeable support layer is viscous or thermoplastic; The base membrane has a medium release layer on one side adjacent to the ultrafiltration layer, and a light release layer on the other side; the outermost permeable support layer has a self-adhesive layer on its outer surface, or the resin coating of the outermost permeable support layer is directly made of self-adhesive resin; Alternatively, the side of the base membrane adjacent to the ultrafiltration layer is a medium release layer, the outermost permeable support layer has a hot melt adhesive layer on its outer surface, or the resin coating of the outermost permeable support layer is directly made of hot melt adhesive resin.

2. A pre-coating film according to claim 1, characterized in that: The resin coating is a polyurethane resin layer, and the base film is a biaxially stretched polyester film.

3. A pre-coating film according to claim 1, characterized in that: The inorganic particles are made by grinding ceramic materials with porous and loose skeleton structures.

4. A pre-coating film according to claim 1, characterized in that: The inorganic nanoparticles have a particle size between 2 and 1000 nanometers.

5. A pre-coated film, characterized in that: The invention comprises a base membrane, an ultrafiltration layer and a water-permeable support layer, wherein the base membrane, the ultrafiltration layer and the water-permeable support layer are stacked in sequence; the base membrane is a plastic film; the water-permeable support layer is thicker than the ultrafiltration layer; The ultrafiltration layer is composed of a resin coating, in which inorganic nanoparticles are evenly distributed; the water-permeable support layer is composed of a resin coating, in which inorganic particles are evenly distributed; the particle size of the inorganic particles in the water-permeable support layer is larger than the particle size of the inorganic nanoparticles in the ultrafiltration layer; The number of layers of the water-permeable support layer is one layer, and the surface of the water-permeable support layer is sticky or thermoplastic; The base membrane has a medium release layer on one side adjacent to the ultrafiltration layer, and a light release layer on the other side; the outer surface of the water-permeable support layer is coated with a self-adhesive layer, or the resin coating of the water-permeable support layer is a self-adhesive resin; Alternatively, the side of the base membrane adjacent to the ultrafiltration layer is a medium release layer, the outer surface of the water-permeable support layer is coated with a hot melt adhesive layer, or the resin used in the resin coating of the water-permeable support layer is a hot melt adhesive resin.

6. A pre-coating film according to claim 5, characterized in that: The resin coating is a polyurethane resin layer, and the base film is a biaxially stretched polyester film.

7. A pre-coating film according to claim 5, characterized in that: The inorganic particles are made by grinding ceramic materials with porous and loose skeleton structures.

8. A pre-coating film according to claim 5, characterized in that: The inorganic nanoparticles have a particle size between 2 and 1000 nanometers.

Citation Information

Patent Citations

  • Pre-coating film

    CN218166568U